Reviewing the Afl S Vilification Laws Rule 35, Reconciliation and Racial Harmony in Australian Football - Gorman, Sean; Lusher, D.; Reeves, K. (Routledge, 2016)
This book is the outcome of an Australian Research Council (ARC) funded project titled Assessing the Australian Football League's Racial and Religious Vilification Laws to Promote Community Harmony, Multiculturalism and Reconciliation, ...